Synthesis, Anti-hypertensive Effect of a Novel Angiotensin II AT1 Receptor Antagonist and its Anti-tumor Activity in Prostate Cancer - Da, Y.-J.; Yuan, W.-D.; Zhu, L.-F.; Chen, Z.-L. (Arzneimittelforschung, 2012)
Since the first non-peptide Ang II receptor antagonist was originally reported, it has become the most common target in the development of new treatments for hypertension. In recent years, all components of the classical RAS have been reported in the prostate, these results suggest the possibility that ARB is a novel therapeutic class of agents for prostate cancer. In this study, a new compound 2-(4-((2-propyl-5-nitro-1H-benzo[d]imidazol-1-yl) methyl)-1H-indol-1-yl) benzoic acid was synthesized and evaluated as a novel angiotensin II AT1 receptor antagonist by radioligand binding assays, anti-hypertensive assays in vivo and oral acute toxicity test. MTT assays and tests in nude mice were used to demonstrate its anti-tumor activity. This new compound showed high affinity to AT1 receptor and anti-hypertensive activity in spontaneously hypertensive rats and renal hypertensive rats. Moreover, in human prostate cancer cells and in athymic nude mice bearing human prostate cancer cells, we observed this new compound had an efficient antiproliferative activity in vitro and anti-tumor activity in vivo. The preliminary pharmacological characteristics with oral acute toxicity test suggested that this new compound can be considered as a candidate for both anti-hypertensive and anti-tumor drug.
Keywords: angiotensin II; AT1 receptor; synthesis; hypertension; prostate; cancer